Understanding the Renal Fibrotic Process in Leptospirosis - Prado, Luan; Barbosa, Angela (International journal of molecular sciences, 2021)
Leptospirosis is a neglected infectious disease caused by pathogenic species of the genus Leptospira. The acute disease is well-described, and, although it resembles other tropical diseases, it can be diagnosed through the use of serological and molecular methods. While the chronic renal disease, carrier state, and kidney fibrosis due to Leptospira infection in humans have been the subject of discussion by researchers, the mechanisms involved in these processes are still overlooked, and relatively little is known about the establishment and maintenance of the chronic status underlying this infectious disease. In this review, we highlight recent findings regarding the cellular communication pathways involved in the renal fibrotic process, as well as the relationship between renal fibrosis due to leptospirosis and CKD/CKDu.